Evidence of transplacental transmission of Encephalitozoon cuniculi genotype II in murine model - Kotková, Michaela; Sak, Bohumil; Hlásková, Lenka; Květoňová, Dana; Kváč, Martin (Experimental parasitology, 2018)
Microsporidia are obligate intracellurar unicellular parasite of wide range of vertebrates. Although ingestion or inhalation of microsporidian spores is the main route of infection, assumed vertical transmission was described in some mammals. The present study was focused on proof of vertical transmission in mice under experimental conditions. Mice were infected with E. cuniculi genotype II intraperitoneally after mating, or perorally followed by mating in acute or chronic phase of infection. Fetuses were delivered by Caesarean section or mice were kept up to the parturition. Some of cubs were immediately after birth transferred to uninfected surrogate mothers. Group of cubs was immunosuppressed. All cubs were examined using polymerase chain reaction for the presence of Encephalitozoon after birth or in their age of 3 or 6 weeks, respectively. All fetuses delivered by Caesarean section, which were intraperitoneally or perorally infected were negative as well as all neonatal mice and youngsters tested in age of 6 weeks. Only immunosuppressed cubs and cubs of immunodeficient mice in age of 21 days were positive for Encephalitozoon cuniculi genotype II. Present results provided the evidence that transplacental transmission of Encephalitozoon cuniculi in mice occurs, but the mechanism of these transport is still unknown.
Keywords: Mice, Inbred BALB C; genotyp; Cercopithecus aethiops; těhotenství; Transplacental transmission; Genotype; DNA fungální; Spores, Fungal; Mice, SCID; Disease Models, Animal; Vero Cells; Encephalitozoonosis; Infectious Disease Transmission, Vertical; Mice; spory hub; SCID; encephalitozoonóza; modely nemocí na zvířatech; ženské pohlaví; Microsporidia; zvířata; Pregnancy; Encephalitozoon cuniculi; BABL/c; DNA, Fungal; vertikální přenos infekce; myši inbrední BALB C; Immunocompromised Host; myši; Chlorocebus aethiops; myši SCID; Female; Vero buňky; imunokompromitovaný pacient; Animals